STUDY OF DRUG INTERACTION POTENCY ON DIABETES MELLITUS PATIENTâS PRESCRIPTION IN OUTPATIENT GUNUNG JATI HOSPITAL CIREBON CITY - Susilo, Rinto (Journal of Pharmacopolium, 2018)
Diabetes Mellitus (DM) is a group of metabolic diseases with characteristics of hyperglycemia that occur due to abnormalities in insulin secretion, insulin performance or both. Drug interactions are one of the drug-related problems that can affect patient therapy. The possibility of drug interactions increasing 2.5 times for each drug added to the patients prescription, and in patients with diabetes mellitus is more susceptible to side effects from drug interactions. This study was conducted to find out what the number of potential events of drug interactions, how the severity of drug interactions, and how the type and amount of diabetes mellitus drugs interacted at the Outpatient Gunung Jati Hospital in Cirebon City. This research was conducted with observational design with descriptive analysis method by taking retrospective DM patient prescription data in January 2018. The results showed that from 100 prescriptions stated as a sample, 84 prescriptions (84%) experienced potential drug interactions, and 84 prescriptions there were 425 occurrences of drug interactions, potential drug interactions based on the severity, the number of incidence drug interactions of strict monitor/ significant / moderate were 291 (68.14%), minor were 120 (28.10%), serious were 15 (3.51%) and contra indication were 0 (0%). The results of the study of antidiabetic mellitus drugs that caused the most potential drug interactions, namely metformin, were 115 events.Â Keywords: Diabetes Mellitus (DM), Drug Interaction Potential, Gunung Jati Hospital Cirebon City.